2019
DOI: 10.1038/s41467-019-10851-4
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the transmetalation step with aryl-zincates in nickel-catalyzed enantioselective arylation of secondary benzylic halides

Abstract: Nickel-catalyzed asymmetric cross-coupling of secondary alkyl electrophiles with different nucleophiles represents a powerful strategy for the construction of chiral tertiary carbon centers. Yet, the use of aryl Grignard reagents or aryl zinc halides in many reactions typically resulted in low enantioselectivity, mainly due to their slow transmetalation step in the catalytical cycle and consequently the requirement of relatively high temperature. Here we report that the use of lithium aryl zincate [Ph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Subsequently, the Ir complex 29, excited by blue-light irradiation can establish a Dexter-type energy transfer (EnT) with the Au(I) intermediate, promoting it into an excited state (30*). The excited complex 30* is likely to undergo oxidative addition with the electrophilic partner (26) and provide the cross-coupling product 27 after reductive elimination. Various control experiments (including NMR, photochemical spectroscopic and theoretical studies) confirmed that this EnT markedly increases the ability of the Au(I) complex 30* to undergo oxidative addition.…”
Section: Visible-light Promoted Oxidative Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the Ir complex 29, excited by blue-light irradiation can establish a Dexter-type energy transfer (EnT) with the Au(I) intermediate, promoting it into an excited state (30*). The excited complex 30* is likely to undergo oxidative addition with the electrophilic partner (26) and provide the cross-coupling product 27 after reductive elimination. Various control experiments (including NMR, photochemical spectroscopic and theoretical studies) confirmed that this EnT markedly increases the ability of the Au(I) complex 30* to undergo oxidative addition.…”
Section: Visible-light Promoted Oxidative Additionmentioning
confidence: 99%
“…In addition to oxidative addition, transmetalation of a nucleophile onto the metal center, and reductive elimination of the nucleophile-electrophile adduct, are also the elementary and fundamental steps in a catalytic cycle for crosscoupling reactions. Significant advances have been made in the nature of transmetalation agents [24][25][26], expanding the range of nucleophiles available for such transformations. Rational ligand design has provided systems that can promote reductive elimination from metal centers that are usually reluctant to undergo this process.…”
Section: Visible-light Promoted Reductive Elimination/transmetalationmentioning
confidence: 99%
“…34 Shen subsequently developed the related Ni/pyridine-oxazoline ligand L8-catalyzed enantioconvergent cross-coupling of racemic CF3 benzyl bromides 33 with arylborates 34 generated from the parent arylboronates and BuLi (Scheme 13). 35 Notably, ZnBr2 was the crucial additive, which dramatically accelerated the transmetalation process via the formation of the corresponding arylzincate species. The successful use of benzylic halides 33 is complementary to the reaction with the alkyl halides 30 in Scheme 12.…”
Section: Substitution With A-halo Cf3 Compoundsmentioning
confidence: 99%
“…[ 3 ] However, while drug chirality has seen its importance and thus emerged as one major theme in drug research and development in the past decades, the utility of chiral fluorine‐containing compounds featuring a trifluoromethylated stereogenic carbon center is still underdeveloped due to lack of feasible methods for enantioselective syntheses of such chiral molecules. Moreover, the precedented protocols for asymmetric construction of trifluoromethylated stereogenic carbon centers usually relies on skeletal divergence at bond‐ forming site, resulting in positioning of this CF 3 ‐substituted carbon at specific spots [ 8,13 ] like benzyl, [ 4,6,11 ] allylic, [ 12 ] or ɑ‐position of heteroatoms, [ 5,9‐10 ] etc . [ 7 ] A general, highly efficient and enantioselective strategy for diverse synthesis of enantiopure alkanes featuring trifluoromethyl‐substituted stereocenters remains elusive but extremely desired.…”
Section: Background and Originality Contentmentioning
confidence: 99%